PROFIL PASIEN KONFIRMASI COVID-19 YANG DIRAWAT DI RSD IDAMAN BANJARBARU PERIODE 2020-2021 - Adilah, Fasya Nur; Muthmainah, Noor; Skripsiana, Nika Sterina; Yuniarti, Rina; Rahmiati, Rahmiati (Homeostasis, 2023)
Corona Virus Disease 2019 (COVID-19) is an infectious disease caused by SARS-CoV-2. The purpose of this study was to determine the profile of COVID-19 confirmed patients being treated at Idaman Banjarbaru Hospital for the 2020 -2021 period based on demographic characteristics, comorbidities, and clinical manifestations. This research method was descriptive retrospective with data collection through patient medical records. The sampling technique used is quota sampling. The subjects of this research is 317 patients. The results showed that the dominant patient characteristics were in the age range of 46-59 years (39.1%), male gender (53.6%), high school education (40.4%) and private sector employee (27.4%). Most of the patients had comorbidities (50.8%). The most comorbid disease was hypertension (67.1%). Based on clinical symptoms, more patients had cough (68.5%).